G141(P) Non-Bacterial Meningitis Notifications to a BPSU Study of Bacterial Meningitis in Babies 0–90 Days of Age in the UK and the ROI. (4th June 2013) - Okike, I; Anomelechi, E; Heath, P
Abstract : Background and Aims: For over 25 years, the BPSU surveillance system has been used to successfully study the epidemiology of very rare diseases in the UK and the ROI. Some notifications usually do not meet study definition. It is possible to get useful clinical information from such notifications when the study questionnaires are completed also. We therefore set out to review the non-bacterial meningitis notifications during our study. Methods: We reviewed all reports that were sent to our study from all sources during the surveillance period and extracted the cases where the clinician completed the study questionnaire and the report did not meet our analytical definition. A descriptive analysis was subsequently undertaken. Results: 868 notifications were received during the study period, 365 unique reports met our case definition. The rest were either duplicates, non-cases or unable to verify. The first 46 non-cases where a questionnaire was also completed were evaluated. 18 (39%) had no CSF sample or culture result, 15 (33%) viral meningitis, 5 (11%) UTI, 4 (9%) sepsis, 3 (7%) was contaminant and 1 (2%) congenital hydrocephalus. The median age (IQR) for the viral meningitis cases was 35.5 days (19–48), 10(67%) were male. The reported presenting features were fever 14 (93%), irritability 12 (80%), poor feeding 10 (66%), lethargy 8 (53%), poor perfusion 7 (47%), vomiting 2 (15%) and comatose 1(7%). The median (IQR) CSF white cell count and CSF protein for the viral meningitis cases was 334/mm 3 (120–475) and 0.85g/L (0.59–1.28) respectively. Overall, two deaths were observed (one was a premature baby with multiple problems and the other died of Coxsackie meningitis). Conclusion: We have been able to evaluate the clinical features of viral meningitis in this age group Further analysis needs to be done to compare the viral meningitis with the bacterial cases.